Transliteracy the latest stage of the literacy continuum - Andretta, Susie (Nordic Journal of Information Literacy in Higher Education, 2010)
The term transliteracy describes “a unifying perspective on what it means to be literate in the 21st Century [including] the ability to read, write and interact across a range of platforms, tools and media from signing and orality through handwriting, print, TV, radio and film, to digital social networks” (Thomas, 2009). This is an interactive session which has two aims. First, it examines transliteracy as the new literacy of the 21st Century by establishing the profile of users who are active and critical producers of content, rather than ‘passive’ consumers of information, and by presenting examples of participative learning promoted by Web 2.0 technologies. Secondly, it assesses the impact of transliteracy practices in terms of enhancing the status of the information professionals, while at the same time fostering the academic and professional development of the learners these professionals support. The topics discussed in this session are relevant to practitioners who are already promoting transliteracy within a Web 2.0 information environment as well as those practitioners who are interested in adopting transliteracy practices to foster participative and reflective learning in their users.